Chelating chloride using binuclear lanthanide complexes in water - Alexander, C; Thom, JA; Kenwright, AM; Christensen, K; Sørensen, TJ; Faulkner, S (Royal Society of Chemistry, 2022)
Halide recognition by supramolecular receptors and coordination complexes in water is a long-standing challenge. In this work, we report chloride binding in water and in competing media by pre-organised binuclear kinetically inert lanthanide complexes, bridged by flexible –(CH2)2 – and –(CH2)3 – spacers, forming [Ln2(DO3A)2C-2] and [Ln2(DO3A)2C-3], respectively. These hydrophilic, neutral lanthanide coordination complexes are shown to bind chloride with apparent association constants of up to 105 M−1 in water and in buffered systems. Hydroxide bridging was observed in these complexes at basic pH, which was proven to be overcome by chloride. Thus, these lanthanide complexes show promise towards chloride recognition in biology and beyond. The results described here have clearly identified a new area of anion coordination chemistry that is ripe for detailed exploration.